China’s Trade and Investment in Africa Impact on Development, Employment Generation & Transfer of Technology - Lisimba, Alpha Furbell (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2020)
XV, 339 p. 18 illus., 17 illus. in color.